Peran Teknologi Pendidikan Pada Mata Pelajaran Matematika Kelas Iii Di Mi Ma’arif Pademonegoro Sukodono - Nurdyansyah Nurdyansyah; Qorirotul Aini (Universitas Islam Lamongan, 2017)
This study aims to determine the importance of technology role in Mathematics Class III in MI Ma'arif Pademonegoro, knowing the supporting factors and inhibiting factors in the application of Mathematics Class III in MI Ma'arif Pademonegoro.Tenelitian is a type of qualitative research using Qualitative descriptive approach and using field research methods (Field Research). Data collection techniques in this study using interviews, observation and documentation and analyzed by using triangulation analysis techniques consisting of three stages namely 1) data reduction, 2) data presentation, and 3) drawing conclusions.keyword: Education technology, Mathematic